Mahogany seeds extract showed potential immunomodulator by in-silico and in vivo testing - Yati Sumiyati; Alessandro Gunady; Perwira Tua; Warni Warni; Heppy Novia; Emilda (BIO Web of Conferences)
Environmental disturbances such as climate change affect human health both infectious and non-communicable disease. Immunity plays an important role in maintaining body health while the mahogany seed has been used empirically to increase immunity. This study aims to evaluate the potential of mahogany seed as an immunomodulator through an in-silico test by molecular docking and an in vivo test using a hemagglutination method. Docking simulation was done towards 16 bioactive contents using Protein Data Bank, PubChem, Marvinsketch, Chimera, Swissdock and pkCSM. The immunomodulatory effect of 96% ethanol extract was studied in 36 DDY mice, separated into 6 groups: normal, negative and positive groups, also mahogany seed extract with dose of 50mg/kgBW, 100mg/kgBW, and 200mg/kgBW). Cyclophosphamide was used to depress immune system and Sheep Red Blood Cells as antigen. The result for the in-silico study showed Gibbs energy of swietenin C and swietenin E more negative than tocilizumab and complied with Lipinski’s rule. The result of the in vivo showed the average antibody titres of group I-VI were 0.00±0.00; 1.90±0.330; 4.31±0.631; 3.51±1.168; 3.71±0.631; 4.01±1.037, respectively. There was no significant difference between the mahogany seed extract treatments with the positive control (p>0.05). This study concludes that mahogany seed extract has immunomodulatory activity that can be utilized by the community in the prevention of various diseases.